Pengaruh Iklan Terhadap Keputusan Pembelian Mie Lemonilo - Rachmah, Siti Mabrur (International Journal of Social and Management Studies, 2022)
Advertising is one way to introduce or promote products to consumers. Advertising plays an important role in encouraging consumers to make a purchase. Companies must be able to implement the right marketing strategies to create products that suit the wishes and needs of consumers. The purpose of this study was to determine the effect of advertising on the Purchase Decision of Lemonilo Noodles. This research uses quantitative research. The data source of this research is primary data using lemonilo noodle consumers as a sample. The data were collected using accidental sampling with 100 respondents as Mie Lemonilo buyers. This study uses simple regression analysis. The findings of this study indicate that advertising has a significant effect on the Purchase Decision of Lemonilo Noodles.